All‐Dielectric Toroidal Metasurfaces for Angular‐Dependent Resonant Polarization Beam Splitting. Issue 10 (14th March 2021) - Zografopoulos, Dimitrios C.; Algorri, José Francisco; Fuscaldo, Walter; López‐Higuera, José Miguel; Vergaz, Ricardo; Sánchez‐Pena, José Manuel; Karolos, Ion‐Anastasios; Beccherelli, Romeo; Tsioukas, Vassilios E.; Yioultsis, Traianos V.; Kriezis, Emmanouil E.
Abstract: An all‐dielectric metasurface exhibiting a strong toroidal resonance is theoretically designed and experimentally demonstrated as an angular‐dependent resonant polarization beam‐splitter in the microwave K‐band. The metasurface is fabricated by embedding a square periodic array of high‐permittivity ceramic cuboid resonators in a 3D‐printed substrate of polylactic acid. It is demonstrated that by properly selecting the resonator geometry and by tuning the angle of incidence through mechanical rotation, the metasurface can switch between a polarization beam splitting and bandpass or bandstop operation. Such performance is achieved by exploiting the highly asymmetric Fano spectral profile of the toroidal resonance and the very low (high) dispersion of the associated p‐(s‐) polarized mode resulting from the resonant toroidal dipole mode's field profile, as evidenced by both full‐wave and band structure simulations. Theoretically infinite extinction ratios are achievable for polarization beam splitting operation with very low insertion losses and adjustable bandwidth. The experimental demonstration of such a compact, all‐dielectric metasurface expands the research portfolio of resonant metasurfaces toward not only the investigation of the intriguing physics of toroidal modes but also to the engineering of functional millimeter‐wave components for polarization control, for instance, in the context of 5G wireless communication networks. Abstract : Toroidal resonances are an elusive class of electromagnetic excitations, rarely found in natural materials. Here, strong toroidal dipole resonances in all‐dielectric metasurfaces composed of high‐permittivity, low‐loss ceramic resonators are demonstrated. By harnessing their particular polarization‐dependent properties, toroidal metasurfaces for angular‐dependent resonant polarization beam splitting in the microwave K‐band are engineered and experimentally demonstrated.